2020
DOI: 10.3390/land9040100
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Environmental Factors that Affect the Growth and Survival of Greek Fir Seedlings

Abstract: Forests in the montane-Mediterranean zone have only recently began to be affected by wildfires, therefore the knowledge necessary for restoration projects is missing. The aim of the study was to assess the effects of factors related to seedling attributes, weather conditions and site suitability on seedling performance. The characterisation of sites was based on bedrock and soil clay content as well as pre-fire vegetation. Apical growth and survival of seedlings was monitored for four years in Parnitha Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…The minimum annual growth of direct seeding under a given aspect would be influenced by smaller initial height before transplanting. It is consistent with the conclusion demonstrated by Detsis et al (2020) who found that initial height has significant positive effect on annual growth. However, the positive impact might be offset by insufficiently developed root systems for seedling planting (Wennström et al, 1999; Mollá et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The minimum annual growth of direct seeding under a given aspect would be influenced by smaller initial height before transplanting. It is consistent with the conclusion demonstrated by Detsis et al (2020) who found that initial height has significant positive effect on annual growth. However, the positive impact might be offset by insufficiently developed root systems for seedling planting (Wennström et al, 1999; Mollá et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…However, the positive impact might be offset by insufficiently developed root systems for seedling planting (Wennström et al, 1999; Mollá et al, 2006). Additionally, root growth would be limited in the first year after planting because roots outgrowing the seedling cup were removed when transplanting for seedling planting, influencing seedling growth (Detsis et al, 2020; Waiboonya and Elliott, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of vegetation along with grazing can negatively affect tree seedling establishment and result in an expansion of shrublands and grasslands in previously tree-dominated areas. A change in climate, for example a reduction in early summer rainfall crucial for fir growth [35], may have had similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…During the summer of 2007, an unpredictable crown wildfire [30] of high-severity [28] completely burned and destroyed a great part (approx. 60%) of the fir forest, resulting in a considerable degradation of the A. cephalonica habitat [6,13,25,26,31]. Due to the species' extremely limited regeneration potential after fire [6], a long-term reforestation project was carried out the next year by the Forest Service of Parnitha in order to restore the burned fir ecosystem.…”
Section: Study Areamentioning
confidence: 99%
“…Taking into consideration the fact that wildfires were not a common phenomenon in fir ecosystems in the past, many of the above issues concerning post-fire restoration have not been studied at all. Scarce studies have examined the issues pertaining to Greek fir, such as the influence of seedling height and site parameters (shade, competitive vegetation, bedrock, weather conditions) on survival and growth of outplanted A. cephalonica seedlings [25,26]. However, most of the factors affecting reforestation success in a post-fire environment have not been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%